The Operative Efficacy of Decompression and Fixation Surgery for Degenerative Lumbosacral Spondylolisthesis: A Single Institutional Study - Kalhoro, Aurangzeb; Kashif Ahmed; Abdul Sattar M. Hashim (Journal of Postgraduate Medical Institute, 2024)
Objective: To assess the results of lumber decompression and lumbar stabilization for spondylolisthesis. Methodology: A retrospective study was designed and included a record of six years. We included 84 patients with Spondylolisthesis. The Meyerding classification was utilized to classify the extent of vertebral slippage in spondylolisthesis. In the case of spondylolisthesis, we did a decompression and pedicle screw fixation. Z score formula was applied to compare the two preoperative and postoperative outcomes in ODIs and report significant result. Results: The mean age of the patients in the study was 49.79 ± 8.11 years. There were 48 (57.14%) male patients and 36 (42.85%) female patients. Spondylolisthesis occurred at L3-L4 in 11 (13.1%) cases. Among the patients, 72 (85.7%) had moderate, 8 (9.5%) had severe, and 4 (4.7%) had mild ODI. Postoperatively, 69 (95.8%) patients experienced substantial improvement in ODI.Top of Form Conclusion: In patients with a mild to moderate Oswestry Disability Index before surgery, the surgical technique provides superior clinical outcomes and improvement.